Association between kidney stones and urological cancers: results from the NHANES 2007–2020 and Mendelian randomization study - Jinghua Zhong; Jiahao Cheng; Zhijian Zhao; Houmeng Yang; Yongda Liu; Xiaolu Duan; Guohua Zeng (Discover Oncology)
Abstract Background Kidney stones is a common urological disease with a rising incidence in global. The association between kidney stones and urological cancers remains controversial. This study utilized the data from the 2007–2020 National Health and Nutrition Examination Survey (NHANES) and Mendelian randomization (MR) analysis to evaluate the association and potential causal relationship between kidney stones and renal cell carcinoma, bladder cancer, and prostate cancer. Methods Multivariate logistic regression was used to examine the association between kidney stones history and urological cancers, followed by stratified analyses. Subsequently, causal relationships were explored via the inverse variance weighted (IVW), weighted median, and MR-Egger methods. Sensitivity analyses were performed to ensure the robustness of the findings. Results Data from 13,013 individuals (5,138 males) were analyzed. Kidney stones was significantly associated with an increased risk of renal cell carcinoma (OR = 1.92, 95% CI 1.90–1.95, P < 0.001), bladder cancer (OR = 2.749, 95% CI 2.71–2.78, P < 0.001), and prostate cancer (OR = 2.03, 95% CI 2.02–2.04, P < 0.001). However, MR analysis did not provide evidence for a genetic causal relationship between kidney stones and these cancers. Sensitivity analyses confirmed the stability and reliability of the MR results. Conclusion Kidney stones increased the risk of renal cell carcinoma, bladder cancer, and prostate cancer in the US population. MR analysis did not establish a genetic causal relationship between kidney stones and renal cell carcinoma, bladder cancer, and prostate cancer in the European population.